2017
DOI: 10.1016/j.cnsns.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of awareness diffusion and self-initiated awareness behavior on epidemic spreading - An approach based on multiplex networks

Abstract: a b s t r a c tIn this paper, we study the interplay between the epidemic spreading and the diffusion of awareness in multiplex networks. In the model, an infectious disease can spread in one network representing the paths of epidemic spreading (contact network), leading to the diffusion of awareness in the other network (information network), and then the diffusion of awareness will cause individuals to take social distances, which in turn affects the epidemic spreading. As for the diffusion of awareness, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(63 citation statements)
references
References 26 publications
(41 reference statements)
0
61
0
Order By: Relevance
“…These findings suggest a new way of understanding realistic contagions and their prevention. Except for obtaining awareness from aware neighbors, self-awareness induced by infected neighbors is another scenario that currently attracts research attention [113], where it is found that coupling such a dynamical process with disease spreading can lower the density of infection, but does not increase the epidemic threshold regardless of the information source.…”
Section: Dynamics In Multilayer Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest a new way of understanding realistic contagions and their prevention. Except for obtaining awareness from aware neighbors, self-awareness induced by infected neighbors is another scenario that currently attracts research attention [113], where it is found that coupling such a dynamical process with disease spreading can lower the density of infection, but does not increase the epidemic threshold regardless of the information source.…”
Section: Dynamics In Multilayer Networkmentioning
confidence: 99%
“…Example Refs social network ER network SF network multilayer networks awareness changing disease outbreak or (and) individual prevention measures [79,78,80,82,110,81,111,112,113] square lattice random network SF network urban network learning rules deciding disease status [85,84,93,117] square lattice ER network SF network adaptive network multilayer networks social network social/self-motivated protection mechanisms impacting disease status or (and) topology structure [124,79,130,128,125,126,129,133,83,87,89,91,115,116,122,127,132] time-varying network independent evolution of both disease and behavior processes [138,139] adaptive network multilayer networks social network topology properties determining disease status or (and) individual behavior [93,117,118,131,134,141,142] connection and dynamics process evolve according to their respective rules [135,136,137]. For example, Summin et al recently explored how to lower the number of vaccin...…”
Section: Disease-behavior Dynamics Characteristicsmentioning
confidence: 99%
“…Nevertheless, regarding many infectious diseases, such as TB, hepatitis C virus (HCV), influenza, and bacterial pneumonia, their pathogens have multiple forms named as different strains. Recent researches show that numerous infectious diseases are caused by multistrain pathogen . There are many forms of interrelationship between strains.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, several mathematical studies have been done to assess the effects of media campaigns for the control of infectious diseases . In previous studies, it is assumed that the number of awareness programs is implemented proportional to the number of infected individuals by considering media as a dynamic variable or transmission rate as decreasing function of number of infected individuals due to media alerts.…”
Section: Introductionmentioning
confidence: 99%